2021
DOI: 10.1101/2021.06.24.449667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High viral abundance and low diversity are associated with increased CRISPR-Cas prevalence across microbial ecosystems

Abstract: CRISPR-Cas are adaptive immune systems that protect their hosts against viruses and other parasitic mobile genetic elements. Consequently, selection from viruses and other genetic parasites is often assumed to drive the acquisition and maintenance of these immune systems in nature, but this remains untested. Here, we analyse the abundance of CRISPR arrays in natural environments using metagenomic datasets from 332 terrestrial, aquatic and host-associated ecosystems. For each metagenome we quantified viral abun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
5
8
0
Order By: Relevance
“…3B). This is in line with previous studies, which had shown that high CRISPR-Cas diversity is associated with anaerobic growth, high temperatures and non-host environments (1315), all of which are characteristics of cheese environments.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3B). This is in line with previous studies, which had shown that high CRISPR-Cas diversity is associated with anaerobic growth, high temperatures and non-host environments (1315), all of which are characteristics of cheese environments.…”
Section: Resultssupporting
confidence: 93%
“…12/13). This is in line with previous results obtained for the Earth Microbiome Project (15) and supports the idea that spacers targeting highly abundant phages are under positive selection and thus dominant in the community (38). Notably, in our previous study focusing on a single cheese starter culture we had found the opposite pattern.…”
Section: Crispr Spacer Abundances Correlates With Target Abundancesupporting
confidence: 93%
See 3 more Smart Citations